2023
DOI: 10.3390/su15054675
|View full text |Cite
|
Sign up to set email alerts
|

Towards Ethical Consumption Activities among Tourism Firms: Nexus of Environmental Knowledge, CSR Participation and Psychological Social Support

Abstract: Employees’ psychosocial competency and CSR participation help them to achieve pro-environmental knowledge for enhancing ethical consumption behaviors. The aim of this study is to assess the level of social responsibility of tourism firms and also examine the impact of environmental knowledge on ethical consumption. The study further investigates the indirect influence through the mediating role of CSR participation and moderating role of psychological social support (PSS) between environmental knowledge and et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
4
0
1
Order By: Relevance
“…This study used a quantitative approach because it referred to previous research conducted by Adil (2022) and Nassani et al, (2023) on the same topic. The data source used was respondents' answers from questionnaires distributed online.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This study used a quantitative approach because it referred to previous research conducted by Adil (2022) and Nassani et al, (2023) on the same topic. The data source used was respondents' answers from questionnaires distributed online.…”
Section: Methodsmentioning
confidence: 99%
“…The concept of environmental knowledge is useful for addressing ecological issues and reflects how much individuals want to participate in programs and activities to preserve the environment, as well as increase ethical consumption practices (Barnett et al, 2005). Nassani et al (2023) revealed that environmental knowledge is positively related to ethical consumption. Environmental knowledge is the basis of ethical consumption.…”
Section: Environmental Knowledge and Ethical Consumptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pengetahuan ini membantu individu berkontribusi dalam upaya pelestarian lingkungan dan memilih produk ramah lingkungan (Yaqub et al, 2023). Kesadaran terhadap dampak lingkungan mendorong keinginan untuk berpartisipasi dalam kegiatan pelestarian (Nassani et al, 2023).…”
Section: Environmental Knowledgeunclassified